Formulation and characterization studies of microspheres - Anusha, R.; Gayathri, K.; Sindhu, T.; Shahi, Rubana Rahat; Hassan, Rabiul; Afroz, Shaik; Vaishnavi, J. (International Journal of Basic & Clinical Pharmacology, 2025)
In the current scenario of delivering therapeutic agents to the target site requires an efficient drug delivery carrier which can delivery the drug only on the site of action in a sustained and controlled manner among many such carriers microspheres fulfill all the parameters for a potent drug carrier. Microspheres are free flowing powders consists of proteins or synthetic polymers that are biodegradable in nature ranging between 1–1000-micron size. A well-designed controlled drug delivery system can overcome some of the problems of conventional therapy an enhanced the therapeutic efficacy of given drug. Microspheres received much attention not only for prolonged release, but also targeted anticancer drugs. Microspheres can be manufactured by various type of material such as glass, polymers and ceramics microspheres. Microspheres are various types like bioadhesive microspheres, magnetic microspheres, floating microspheres, radioactive microspheres, polymeric microspheres are prepared by methods like spray drying, solvent evaporation, single emulsion, double emulsion, solvent extraction, quassi emulsion solvent diffusion. Microspheres will play a key role in novel drug delivery in the future by fusing together a variety of other strategies especially in diseased cells, diagnostics and act as supplements as miniature versions of diseased organ and tissues in the body.